Teledermatology Evaluation and Feedback Systems: A Tool for Improving Care - Fuenzalida-Cruz, H; Loubies-Muñoz, R (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Chile is a country where teledermatology has been growing exponentially since the implementation of a single national asynchronous teledermatology platform for the public system in December 2018. To ensure the quality of care in teledermatology systems, it is crucial to evaluate the fulfillment of basic specifiers such as ICD-Diagnosis, therapeutic suggestions, and diagnostic suggestions, among others. This article aims to evaluate the teledermatology system of the Chilean public health service by analyzing 243 randomly extracted consultations, representative of the 20,716 electronic consultations performed during 2020. Compliance with basic specifiers is evaluated. From these, fulfillment of core teledermatology functions, such as diagnostic and therapeutic suggestions, is observed in most consultations. There are statistically significant relationships between the patient’s destination (primary health center [PHC] or face-to-face referral), pharmacological prescription, coverage of the drug prescribed by the public system, and the education received by the consulting physician. If the consultation is resolved in the PHC, there is a higher chance for pharmacological prescription, prescribing mostly drugs that are covered by the government. This is less likely to occur when patients are referred for face-to-face evaluation. A targeted evaluation of education, pharmacological prescriptions, and their applicability is key to improving the quality of teledermatology systems. © 2023 by the authors.